Compósitos de cobaltitas/carvão ativo aplicados como eletrocatalisadores na reação de evolução de oxigênio - Lima, Andrei Fellipe Veríssimo de (2021)
Hydrogen gas (H2) has stood out as a clean and renewable source, and an alternative to replace fossil fuels. The water electrolytic splitting is the most advantageous process for obtaining H2, considering environmental issues. The main reactions of water electrolysis are the Oxygen Evolution Reaction (OER) and the Hydrogen Evolution Reaction (HER). However, there is a high consumption of electrical energy caused mainly by OER, and catalysts are an alternative to make this process energetically feasible. Therefore, in this work three composites based on cobaltite and activated carbon (Co3O4/C) were synthesized and applied as electrocatalysts in OER. These composites were obtained via thermal treatment at 350 °C of composites containing ZIF-67 (Zeolitic Imidazolate Frameworks 67) and different percentages of activated carbon (10, 30 and 50% m/m). The three precursor composites (ZIF-67/C) were characterized by X-ray powder diffraction (XRD) and infrared absorption spectroscopy (IR), which showed the characteristic signs of the components, confirming the crystallization of ZIF-67 even at presence of activated coal. The thermal decomposition of the precursors was also evaluated via thermogravimetric analysis (TGA). Co3O4/C electrocatalysts were also characterized by XRD and IR. Powder patterns indicate the formation of cobaltites with cubic crystalline phase, in addition to the presence of amorphous carbon signals, confirming the formation of the composite. These data were also corroborated by infrared spectra, which showed the main vibrations of the organic groups present in the active carbon, as well as the stretches of the Co-O bond. The electrocatalytic performance in the OER was evaluated using cyclic voltammetry and linear scanning voltammetry, in an alkaline medium. Although all composites have been classified as “excellent” according to the literature, Co3O4/C10 performed better, with 321 mV overpotential and a Tafel slope of 71.97 mVdec-1 to obtain a current density of 10 mA cm-2. An inverse relationship was observed between electrocatalytic performance and the amount of coal in the sample. All Co3O4/C composites obtained present an equal or superior performance when compared with similar materials with the literature.